An interpretative phenomenological study about maternal perceptions of cesarean birth. - Hala Bawadi; Zaid Al-Hamdan; Nagham Abu Shaqra; Amer Gharaibeh; Hasan Rawashdeh; Asma Basha; Majida Jallad; Sawsan Majali; Heba AboShindi; Mahmoud Taym (PLoS ONE)
Aim To explore the perceptions of Jordanian primipara and para 1 women regarding Cesarean section delivery and provide insights for clinical practice, policy development, and future research to optimize maternity care practices and outcomes in Jordan and similar contexts. Background Global Cesarean section (CS) rates have risen steadily over recent decades. Jordan has witnessed a significant increase in CS rates. This trend has sparked interest in understanding the underlying factors behind this phenomenon and the perceptions surrounding CS delivery. Understanding these factors is essential for informing healthcare practices and promoting optimal maternal and neonatal health outcomes. Methods Forty-one primipara and para 1 women were interviewed within seven focus groups. The analysis was conducted using interpretative phenomenological analysis with the assistance of the NVivo 12 software program. Results Three main themes were identified: The Foundation of Women's Knowledge and Cognitive Structures; The Influential Parties in Shaping Women's Perceptions; and Transforming Perception into Action. Discussion To offer empathetic, comprehensive, and patient-centered care, healthcare professionals should discuss delivery options with pregnant mothers and factor in maternal preferences and perceptions. This study underscores the importance of supportive dialogue and informed decision-making in maternity care, advocating for a more individualized approach to childbirth.